Influence of 5-Week Snack Supplementation with the Addition of Gelatin Hydrolysates from Carp Skins on Pro-Oxidative and Antioxidant Balance Disturbances (TOS, TAS) in a Group of Athletes - Małgorzata Morawska-Tota; Łukasz Tota; Joanna Tkaczewska (MDPI AG, 2022)
The research objective was to assess the effects of 5-week snack supplementation with added enzymatic hydrolysates from carp skins on shifts in pro-oxidative and antioxidant balance among athletes. The study comprised 49 adults (experimental group (E)-17, placebo (P)-16, control (C)-16) practicing endurance disciplines. Selected somatic indices and maximal oxygen uptake/m (VO2max) were measured. Based on VO2max, an individual exercise intensity was selected with predominating eccentric contractions (60% VO2max). The conducted tests consisted of 2 series (1st-graded and eccentric, 2nd-eccentric). The experimental group consumed a snack with added gelatin hydrolysates from carp skins for 5 weeks in between the series, the placebo-a snack without added hydrolysates, and in the control-no supplementation was implemented. Blood samples were taken before, and 1, 24 and 48 h after completion of the eccentric test. TAS and TOC concentrations in the blood plasma were assessed. No significant changes in TOS/TOC and TAS/TAC concentrations were noted between the 1st and the 2nd test series, before or following the eccentric test in the control and placebo groups. In the measurements performed 1, 24 and 48 h after completion, the observed differences were highly significant (p < 0.001). After 5 weeks of snack consumption, an increase from medium to high antioxidant potential was observed for E. Differences between the 1st and the 2nd test series were of high statistical significance (p < 0.001). The demonstrated differences in pro-oxidative-antioxidant balance indices between successive series allow to confirm antioxidant effects and indicate possibilities for its implementation, not only in sports.